Serotonin transporter 5-HTTLPR genotype moderates the effects of childhood adversity on posttraumatic stress disorder risk: a replication study - Xie, Pingxing (2012)
We reported that the 5-HTTLPR polymorphism in the promoter region of the serotonin transporter gene (SLC6A4) moderates the effect of childhood adversity on posttraumatic stress disorder (PTSD)risk (Xie and others 2009). In the present study, we considered 5178 subjects (a group with generally high substance dependence comorbidity, as for our previous study) using similar methodology to replicate our previous results. We used logistic regression analyses to explore the interaction effect of 5-HTTLPR genotype and childhood adversity on PTSD risk. We found that, as reported in our previous study, in individuals with childhood adversity, the presence of one or two copies of the S allele of 5-HTTLPR increased the risk to develop PTSD. This gene-environment interaction effect was present in European Americans (EAs), but not in African Americans (AAs) (EAs, OR=1.49, 95% CI=1.07–2.08, P=0.019; AAs, OR=0.90, 95% CI=0.60–1.35, P=0.62). The statistical power to detect this interaction effect was increased when data were combined with those from our previous study (Xie and others 2009). The findings reported here replicate those from our previous work, adding to a growing body of research demonstrating that the 5-HTTLPR genotype moderates risk for anxiety and depression phenotypes in the context of stress and adverse events.